Perception, Motivation, and Communicative Self-confidence of Indonesian Students On Willingness to Communicate in L2 By Using Facebook - Fadilah, Eka (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2018)
The present study aims to investigate direct and indirect factors affecting willingness to communicate (WTC) in L2 by using Facebook. Second semester English students (n=156) from private and state universities in three cities in Indonesia; Surabaya, Bali, and Malang participated in this study. A set of questionnaire with a 5-point Likert-scale encompassing students’ perception, motivation, communicative selfconfidence (CSC), and Willingness to Communicate (L2 WTC) was used to collect the data. The data were then analyzed using a software package, AMOS 20, to gauge the magnitude of the factors affecting L2 WTC by using FB platform. The finding reveals that there are considerable effects on perception and motivation mediated by communicative self-confidence to WTC. While, communicative self-confidence shows the strongest predictor on L2 WTC.